PERUBAHAN PERILAKU REMAJA PENGGUNA GAME FREE FIRE DI DESA PENITI KECAMATAN SEKADAU HILIR KABUPATEN SEKADAU - Efendi, Iwan; Sikwan, Agus Sikwan; Prancisca, Stella (Universitas Tanjungpura, 2024)
Mechanical progress can be felt both directly and indirectly. Recently, electronic games or what we usually call web-based games have experienced very rapid development. The main objective of this exploration is to understand changes in the behavior of the younger generation who use free fire games in Peniti, Sekadau Region, Sekadau Regime. This examination uses a subjective exploration strategy and the information gathering methods used are perception, meetings and documentation studies. The resource persons in this exploration are teenagers who play web-based games, guardians and educators. As a result of the exploration and discussions carried out by the creator, it is assumed that the way of behaving using web-based games by the younger generation makes teenagers have a positive and pessimistic way of behaving, more specifically the pessimistic way of behaving of teenagers who play internet games such as fixation, ignoring actual practice and become a protester. Apart from negative changes, web-based games also provide positive social changes such as preparatory fixation abilities, expansion of jargon abilities in English, further development of PC abilities, and preparation of the ability to work together in groups. Web-based games are mostly used for entertainment, but what happens is that online games are played unreasonably, causing social changes in the younger generation